Analisis Pemenuhan Asas Keterbukaan Dalam Perubahan UU TNI 2025 - Wahidil Atma; Arif Wibowo (Universitas Sains dan Teknologi Komputer, 2026)
This research aims to critically analyze the fulfillment of the principle of openness in the formation and substantive content of Law Number 12 of 2025 concerning Amendments to Law Number 34 of 2004 concerning the Indonesian National Armed Forces (2025 TNI Law). The principle of openness is a crucial pillar of a democratic constitutional state, ensuring accountability in the defense sector. The research method employed is normative legal research, with a statutory, conceptual, and historical approach. The results indicate that the legislative process for the 2025 TNI Law did not fully meet the standards for meaningful participation. Although formal access was provided, the substantial involvement of civil society groups and independent legal experts remained severely limited, thereby obscuring the rights to be heard and to be explained. Substantively, there are normative ambiguities regarding the regulation of state secrets and the expansion of civilian positions for active military officers, which may lead to overlapping authorities and reduced government transparency. The lack of clarity in information classification criteria within this law risks reviving a culture of impunity under the pretext of security and stability. This study concludes that the 2025 TNI Law requires further synchronization with the Law on Public Information Disclosure. It is recommended to establish implementing regulations that limitively define the boundaries of state secrets and to strengthen external oversight mechanisms by independent institutions to ensure that the strengthening of military institutions remains aligned with the principles of civilian supremacy and budgetary transparency.